Marketing of innovation in turbulent market: introduction of an ambidextrous marketing innovation paradigm - Nezakati, Hossein *; Sharifirad, Kourosh (2015)
Turbulence, risk and uncertainty are now the normal situation of firms, markets and industries. This normality is underlined by periodic and irregular upturns and downturns which has two main effects. One is vulnerability, against which companies deploy their defensive shield. The latter is opportunity, which should be constantly exploited. This study aims to present a new ambidextrous marketing innovation paradigm for firms which running in a turbulent and complex environment. The model is composed of four main vectors as content, channel, community and context which seem to be influential on stimulating companies' dynamic capabilities to achieve competitive advantage in turbulent markets. It is assumed that these vectors might influence companies' capabilities to tackle their two substantial issues of survival in turbulent environment which are their vulnerability against ever changing environment as well as discovery and exploitation of opportunities. This study is supported by establishing common domain between complex theory, dynamic capability theory and innovation theory. The theoretical underpinning of relationship between innovation approach and turbulent environments are investigated. The approaches suggested by complex theory are contrasted with innovation orientation approaches to evaluate the validity of model. With finding a clear gap in this research area, the proposed model will provide an illustration of how companies might be survived successfully in a complex and turbulent environment.